Three Views of Revolutionary Power in Cuba’s Countryside, 1957–1958 - Eloise Linger (International Journal of Cuban Studies)
This article examines three approaches to explain the rapid success of the revolutionary forces in winning the support of various socio-economic levels of farmers and farmworkers in the rural areas of eastern Cuba, especially in the Sierra Maestra and the Sierra Cristal, 1957–1958. Those last two years of struggle proved decisive for the revolutionary victory in Cuba. An ‘auditor’, the political and judicial leader who also served to procure the needs of the soldiers and local civilians, recounts the approaches of his organisation (the 26 July Movement) in winning over both farmers with varying levels of poverty and wealth, and military officers of Batista’s army. The second viewpoint by two academic researchers covers a longer expanse of time and a wider panorama of conflicting interests and racial divides related to land usage and ownership. Raising some historical antecedents from the early to mid-twentieth century, their analyses challenge the standard historiography of the Revolution that presents “a white, significantly male, and middle-class-led revolution,” thus silencing the experiences of Black Cubans. Radical women and men, including communists, organised in both the labour movement and the struggling rural population in the 1930s and 1940s. Urban resistance was also decisive for the outcome of the insurrection in 1957–1958. A third approach posits that Fidel Castro’s leadership team manipulated local farming communities to believe that he was a messiah or leader sent by God to take Cubans to a secure future. The article considers these approaches alongside other historical accounts.